Good Sport: Developing a Policy to Safeguard High-Performance Athletes from Psychosocial Workplace Hazards - Rew, Quentin (New Zealand Journal of Health and Safety Practice, 2025)
This paper explores the New Zealand (NZ) high-performance sport industry from the perspective of occupational health and safety (OHS). High-performance athletes face significant psychosocial stresses and hazards in the course of their work, which have not been sufficiently addressed through top-down leadership, or safe systems of work. This paper outlines best practice for managing psychosocial hazards in the NZ high-performance sport industry, culminating in a proposed safeguarding policy. The “Proposed HPSNZ Policy: Wellbeing and Mental Health Support for High-Performance Athletes” is grounded in international best practice incorporating literature from OHS, hauora Māori (Māori health), and sport psychology. If implemented by High Performance Sport NZ (HPSNZ), this policy could safeguard NZ high-performance athletes from psychosocial workplace hazards. Such a policy was recommended following the death of NZ Olympian Olivia Podmore, and this paper presents a viable option allowing HPSNZ to fulfil that recommendation.